Leafminers on Ornamental Plants - Eileen A. Buss (EDIS)
Revised! ENY-326, a 4-page illustrated fact sheet by Eileen A. Buss, describes larvae that feed between the upper and lower surfaces of leaves, creating serpentine or blotchy tunnels inside the leaves, including specific sections on Azalea Leafminers, Yellow Poplar Weevils, Blotch Leafminers, Citrus Leafminers, and methods of control for this type of pest. This version is updated to include links to additional information and a new table listing insecticides labeled for use by homeowners against leafminers in Florida, in addition to the listing of those registered for professional use. Part of the Master Gardener Handbook. Originally published by the UF Entomology and Nematology Department, October 1993. Revised June 2006.